On the empirics of aid and growth: A fresh look - Jan-Erik Antipin; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The paper contributes to the empirics of aid and growth by taking a fresh look at the aid-policies-growth nexus emanating from the very influential but also debatable paper on the subject by Burnside and Dollar: `Aid, Policies and Growth'. We employ three different datasets (including the one used in the Burnside and Dollar paper) and Bayesian instrumental variable methods to test the robustness of the central finding of the Burnside and Dollar paper related to the aid and policy interaction coefficient. In doing so, we applied Bayesian instrumental variable techniques to find the most probable parameter values in the growth equation. We also test for the exogeneity of the instrumental variables used. We find that the marginal effect of the disputed (Aid/GDP) x Policy variable on real per capita GDP growth is substantially smaller than in Burnside and Dollar, thus casting serious doubts on the robustness of their findings, and most importantly, on the validity of the policy lessons emerged from the Burnside- Dollar study. – aid ; growth ; policies ; aid effectiveness ; Bayesian instrumental variable methods
Keywords: F35; 330; Entwicklungshilfe; Theorie; Makroökonomischer Einfluss